Release characteristics of chitosan treated alginate beads: I. Sustained release of a macromolecular drug from chitosan treated alginate beads - SEZER, ALİ DEMİR (TAYLOR & FRANCIS LTD, 1999)
Alginate and chitosan treated alginate beads were prepared and compared as an oral controlled release system for macromolecular drugs. Dextran (M.W. 70 000) was used as a model substance. The beads were prepared by the ionotropic gelation method and the effect of various factors (alginate, chitosan, drug and calcium chloride concentrations, the volume of external and internal phases and drying methods) on bead properties were investigated. The addition of chitosan increased the drug loading capacity of the beads, and larger beads were obtained in the presence of chitosan. On the other hand, addition of chitosan in the gel structure reduced the drug release from beads. The erosion of the beads was suppressed by chitosan treatment. The drying method was important to the properties of the chitosan-alginate beads. It is proposed that chitosan treated alginate beads may be used as a potential controlled release system of such macromolecules.
Keywords: beads; alginate; chitosan; controlled release; macromolecules; GEL MATRIX; DELIVERY; EROSION; BLUE